Transformation by Modeling MOF 2.0 QVT: From UML to MVC2 Web model - Esbai, Redouane; Erramdani, Mohammed; Mbarki, Samir; Arrassen, Ibtissam; Meziane, Abdelouafi; Moussaoui, Mimoun (INFOCOMP Journal of Computer Science, 2011)
The continuing evolution of business needs and technology makes Web applications more demanding in terms of development, maintenance, and management. To cope with this complexity, several frameworks have emerged. Given this diversity of solutions, the generation of a code based on UML models has become important. This paper presents the application of the MDA (Model Driven Architecture) to generate, from the UML model, the Code following the MVC2 pattern (Model-View-Controller) using the standard MOF 2.0 QVT (Meta-Object Facility 2.0 Query-View-Transformation) as a transformation language. This standard defines the meta-model for the development of model transformation. The transformation rules defined in this paper can generate, from the class diagram, an XML file containing the Actions, the Forms, and JSP pages. This file can be used to generate the necessary code of a web application.